2023
DOI: 10.3390/curroncol30060422
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Lived Experiences with Cancer-Related Cognitive Impairment: An Exploratory Qualitative Study

Abstract: Cancer-related cognitive impairment (CRCI; e.g., disrupted memory, executive functioning, and information processing) affects many young adults, causing significant distress, reducing quality of life (QoL), and thwarting their ability to engage in professional, recreational, and social experiences. The purpose of this exploratory qualitative study was to investigate young adults’ lived experiences with CRCI, and any strategies (including physical activity) they use to self-manage this burdensome side effect. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Indeed, CRCI can have a substantial and lasting effect on the lives of YA cancer survivors who are undergoing critical transition points in forming social bonds and working toward educational and career goals. 22,23 Cognitive, educational, and vocational rehabilitation interventions could be strengthened by tailoring intervention content to address the unique needs of YA cancer survivors and the specific impacts of CRCI. For example, interpersonal effectiveness skills training could be incorporated to prevent or address misunderstandings from others regarding YA cancer survivors' intentions when they are unable to recall names or need additional time to process new information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, CRCI can have a substantial and lasting effect on the lives of YA cancer survivors who are undergoing critical transition points in forming social bonds and working toward educational and career goals. 22,23 Cognitive, educational, and vocational rehabilitation interventions could be strengthened by tailoring intervention content to address the unique needs of YA cancer survivors and the specific impacts of CRCI. For example, interpersonal effectiveness skills training could be incorporated to prevent or address misunderstandings from others regarding YA cancer survivors' intentions when they are unable to recall names or need additional time to process new information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these more problem-focused coping strategies, 28 provided survivors the ability to adapt to their CRCI. 23 In contrast, forcing oneself to "power through" (ID 20) and perform at the same level as their pre-cancer abilities was described as creating an unhelpful spiral of stress that worsened their cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms can cause changes in work activities, exercise, household duties, hobbies, and affect relations to both family and friends. Typical work-related activities that are affected by CRCI and CIPN include planning, scheduling, driving, typing, standing, and manual work (202)(203)(204). A newly published study found that 30.4% of patients with central or peripheral neuropathy due to chemotherapy were forced to change work activities in relation to their symptoms, and 35.5% had reduced their work time from full-time to part-time.…”
Section: The Impact Of Cancer-related Cognitive Impairment and Chemot...mentioning
confidence: 99%